FPGA Based Control Method for Three Phase BLDC Motor - Suneeta Suneeta; R Srinivasan; Ram Sagar (Institute of Advanced Engineering and Science, 2016)
This paper introduces a good method which is helpful to assist in the design and control of cost effective, efficient Brushless Direct Current (BLDC) motors. Speed Control of BLDC motor using PIC microcontrollers requires more hardware, and with the availability of FPGA versatile features motivated to develop a cost effective and reliable control with variable speed range. In this paper, an algorithm which uses the Resolver signals captured from the motor is developed with the help of Resolver to Digital converters. The program has been written using VHDL. This program generates the firing pulses required to drive the MOSFETs of three phase fully controlled bridge converter driven by drivers. Then the program has been loaded on the Spartan- 3 FPGA device and tested on the 30V, 2000 rpm BLDC motor which can make the motor run at constant speed ranging from 10 to 2000 rpm. The proposed hardware and the program are found to be very good and efficient. The results are good compare to PIC Microcontroller based design.